L protease from foot and mouth disease virus confers eIF2‐independent translation for mRNAs bearing picornavirus IRES. Issue 21 (28th September 2014) - Moral-López, Pablo; Alvarez, Enrique; Redondo, Natalia; Skern, Tim; Carrasco, Luis
Abstract : The leader protease (L pro ) from foot‐and‐mouth disease virus (FMDV) has the ability to cleave eIF4G, leading to a blockade of cellular protein synthesis. In contrast to previous reports, our present findings demonstrate that FMDV L pro is able to increase translation driven by FMDV IRES. Additionally, inactivation of eIF2 subsequent to phosphorylation induced by arsenite or thapsigargin in BHK cells blocks protein synthesis directed by FMDV IRES, whereas in the presence of L pro, significant translation is found under these conditions. This phenomenon was also observed in cell‐free systems after induction of eIF2 phosphorylation by addition of poly(I:C). Abstract : FMDV L pro is able to stimulate translation of mRNAs bearing poliovirus IRES. This stimulation is also found with FMDV IRES when luciferase is measured. L pro confers translatability to mRNAs bearing IRESsafter phosphorylation of eIF2a.